2019
DOI: 10.1021/acsami.8b19787
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Overpotentials and Nucleation Rates for Electrodeposition on Metal Anodes

Abstract: Rechargeable batteries employing metal negative electrodes (i.e., anodes) are attractive next-generation energy storage devices because of their greater theoretical energy densities compared to intercalation-based anodes. An important consideration for a metal's viability as an anode is the efficiency with which it undergoes electrodeposition and electrodissolution. The present study assesses thermodynamic deposition/dissolution efficiencies and associated nucleation rates for seven metals (Li, Na, K, Mg, Ca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 86 publications
0
48
0
Order By: Relevance
“…The surface energies of 0.463 and 0.230 J/m 2 for relaxed BCC Li and Na (100) slabs, respectively, are in good agreement with previous studies. 64 A very small difference in the energy was observed between the as cleaved and relaxed BCC (100) surfaces for both Li and Na. The ( ) and (0001) surfaces of HCP Li are higher 1010 in energy per unit area than the (100) surface of BCC Li.…”
Section: Free Alkali Metal Surfaces Vacancy Segregation At An Alkali Metal Surfacementioning
confidence: 94%
See 2 more Smart Citations
“…The surface energies of 0.463 and 0.230 J/m 2 for relaxed BCC Li and Na (100) slabs, respectively, are in good agreement with previous studies. 64 A very small difference in the energy was observed between the as cleaved and relaxed BCC (100) surfaces for both Li and Na. The ( ) and (0001) surfaces of HCP Li are higher 1010 in energy per unit area than the (100) surface of BCC Li.…”
Section: Free Alkali Metal Surfaces Vacancy Segregation At An Alkali Metal Surfacementioning
confidence: 94%
“…62 Additional corrections to the alkali metal surface energy such as those in ref 63 were not included, although they are expected to be small for Li and Na from previous work. 64 For the substrate phases, which were not subjected to a strain, the bulk energy, , was calculated from fully optimised, periodic unit cell structures of each material.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the room temperature solubility of Li in Au, Ag and Mg enables the formation of a surface solid solution layer upon lithiation at the interface without the need for heterogeneous nucleation, thereby eliminating the overpotential associated with the nucleation process. This surface layer also alters the morphology of the deposited Li [33][34][35] . Furthermore, studies have shown 'dead Li' formation depends more on the nucleation process, rather than the subsequent growth 36-38 . Therefore, it can be inferred that a substrate with preferred nucleation can decrease the dead Li formation and improve the cycling Coulombic efficiency.…”
Section: Plating On Top Of the Coatingmentioning
confidence: 99%
“…Li{100} was selected due to its high surface stability. 51 Simulations including LiPF6 as a control were also investigated to highlight the difference between the LiPF6 present in conventional electrolytes and the KPF6 added to our electrolytes. Based on DFT optimized geometries, we measure and compare the atomic bond distances formed between the atoms of electrolytes, alkali salts and the Li surface as an indicator of the extent of chemical reaction.…”
Section: K + -Solvent Ion Pair Formation Suppresses Electrolyte Decommentioning
confidence: 99%